The Effects of High Performance Work Practices on Job Satisfaction in the United States Steel Industry - Berg, Peter (Relations industrielles / Industrial Relations, 1999)
A unique data set is used to examine how different practices associated with high performance work systems in the steel industry affect the job satisfaction of workers. While the effect of these practices on organizational performance is widely studied, few have examined their effects on workers. Their analysis in this paper is based on data from a sample of 1,355 hourly workers in the US steel industry across 13 plants. The results indicate that the effect of high performance practices on job satisfaction depends primarily on how work roles and job duties are defined, on good employee-management relations and on practices that help balance work and family responsibilities. These results show that those who are able to use their skills and knowledge on the job, those who report positive employee-management relations, and those who believe the company helps them balance work and family responsibilities have relatively high probabilities of being very satisfied with their jobs.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Job satisfaction; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Statistical analysis; Steel industry; Studies; Work environment